Pre-operative assessment of impacted mandibular third molar and inferior alveolar canal using orthopantomograhpy and cone beam computed tomography (Bangabandhu Sheikh Mujib Medical University Journal, 2016)
The aim of this study was to assess the proximity and relation of impacted mandibular third molar and inferior alveolar canal on orthopantomogram and cone beam computed tomography (CBCT). Sixty impacted mandibular third molars having close proximity with the  inferior alveolar canal were included. CBCT images were done to determine the exact location and relationship of impacted third molar tooth and inferior alveolar canal. We assessed the radiographic signs from orthopantomogram, the course of  inferior alveolar canal and proximity to the third molar tooth in CBCT. The buccal course of  inferior alveolar canal was most frequently detected (n=36) in CBCT findings. The impacted lower third molar roots were 55% contact with the  inferior alveolar canal and 45% separate from the canal. On orthopantomogram, the following signs were strongly correlated with actual contact: Superimposed relationship between the third molar and the inferior alveolar canal. CBCT is useful as a presurgical planning in patients with impacted mandibular third molar showing close proximity to the  inferior alveolar canal.